Nucleation Mechanisms of Aromatic Polyesters, PET, PBT, and PEN, on Single-Wall Carbon Nanotubes: Early Nucleation Stages. (4th October 2012) - Espinoza-Martínez, Adriana; Avila-Orta, Carlos; Cruz-Delgado, Víctor; Olvera-Neria, Oscar; González-Torres, Julio; Medellín-Rodríguez, Francisco
Abstract : Nucleation mechanisms of poly(ethylene terephthalate) (PET), poly(butylene terephthalate) (PBT), and poly(ethylene naphthalate) (PEN) on single-wall carbon nanotubes (SWNTs) are proposed, based on experimental evidence, theoretical epitaxy analysis, and semiempirical quantum chemical calculations. In order to elucidate early nucleation stages polyester-coated nanotubes were obtained from highly diluted solutions. High-resolution transmission electron microscopy (HRTEM) revealed helical morphologies for PET/SWNTs and PEN/SWNTs and the formation of lobules with different orientations for PBT/SWNTs. To explain the morphological behavior one model was proposed based on crystallographic interactions, that is, epitaxy. Theoretical epitaxy calculations indicated that epitaxy is not possible from the strict epitaxy point of view. Instead, aromatic self-assembly mechanism was proposed based on π - π interactions and the chirality of the nanotube. It was proposed that the mechanism implies two steps to produce helical or lobular morphologies with different orientations. In the first step polymer chains were approached, aligned parallel to the nanotube axis and adsorbed due to electrostatic interactions and the flexibility of the molecule. However, due to π - π interactions between the aromatic rings of the polymer and the nanotube, in the second step chains reoriented on the nanotube surface depending on the chirality of the nanotube. The mechanism was supported by semi-empirical calculations.